A Bayesian Regression Analysis of the Effects of Narcissism on Group Performance - Gunnesch-Luca, George; Paul, Karsten Ingmar; Moser, Klaus (Journal of Personnel Psychology, 2023)
Though people high in narcissism have high self-esteem and appear as charming, their long-term relationships are problematic due to their difficult interpersonal style, which suggests that maintaining sound exchange relationships with narcissists is difficult. Because work teams must rely on continuing and reliable exchange processes, narcissistic team members should be detrimental to their functioning. We investigated this hypothesis by collecting data from 110 work groups from various organizations and analyzing the association between narcissism-based group composition indices and team performance. Using Bayesian inference, the results show that narcissism in work groups is negatively related to interpersonal forms of citizenship behavior, but not to citizenship behaviors that target the organization. Furthermore, group task performance was also negatively affected by narcissism within the tea
Keywords: teams; narcissism; unit-level performance; unit-level OCB; Bayes